Reaksi Pasar Terhadap Pengumuman Pembelian Kembali Saham (Buy Back) Pada Perusahaan yang Terdaftar di BEI tahun 2013-2014 - Komaeroh, Siti; Salim, Ubud (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to determine the market reaction to the share repurchase (buy  back)  announcement  that are  indicated  by  the  change of abnormal  return and share  trading volume activity  significantly. The model of this  research  is event  study which conducted by using 18 companies as  samples, which perform buy backing at period 2013-2014 in the Indonesia Stock Exchange (IDX). The sampling technique of this study is purposive sampling method. Based On the result of hypothesis testing, this study found that investors perform significant  reaction  to  the  buy  back  announcement as  which  appeared  by the average  trading  volume  activity of  all-day  observation  period. However,  this study  did  not  find  any  significant  average  abnormal  return (AAR)  among  the share  repurchase  announcement (buy  back), and  also  did  not  find  differences on average of abnormal return and average of trading volume activity before and after  the buy back announcement. This occurs due  to  investors  tend  to act "wait and see" so  the reaction  that proved by significant AAR cannot be observed  in a short period of  time. In short,  the buy back announcement which  is conducted by market  responded positively  to  the  increase of  trading volume, but has not been able to raise the AAR significantly in a short period of time. Keywords:  event  study,  the  buy  back  announcement,  IDX,  abnormal  return, trading volume activity